Muscle as a Secretory Organ. Issue 3 (July 2013) - Pedersen, Bente K.
Abstract: Skeletal muscle is the largest organ in the body. Skeletal muscles are primarily characterized by their mechanical activity required for posture, movement, and breathing, which depends on muscle fiber contractions. However, skeletal muscle is not just a component in our locomotor system. Recent evidence has identified skeletal muscle as a secretory organ. We have suggested that cytokines and other peptides that are produced, expressed, and released by muscle fibers and exert either autocrine, paracrine, or endocrine effects should be classified as "myokines." The muscle secretome consists of several hundred secreted peptides. This finding provides a conceptual basis and a whole new paradigm for understanding how muscles communicate with other organs such as adipose tissue, liver, pancreas, bones, and brain. In addition, several myokines exert their effects within the muscle itself. Many proteins produced by skeletal muscle are dependent upon contraction. Therefore, it is likely that myokines may contribute in the mediation of the health benefits of exercise. © 2013 American Physiological Society. Compr Physiol 3:1337‐1362, 2013.